2022
DOI: 10.1182/blood.2021012091
|View full text |Cite
|
Sign up to set email alerts
|

PEG10 amplification at 7q21.3 potentiates large-cell transformation in cutaneous T-cell lymphoma

Abstract: Mycosis fungoides (MF), the most common form of cutaneous T-cell lymphoma, undergoes large-cell transformation (LCT) in the late stage, manifesting aggressive behavior, resistance to treatments, and poor prognosis, but the mechanisms involved remain unclear. To identify the molecular driver of LCT, we collected tumor samples from 133 MF patients and performed whole-transcriptome sequencing on 49 advanced-stage MF patients, followed by integrated copy number inference and genomic hybridization. Tumors with LCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…To investigate the expression pattern of the IKZF family in CTCL, this study explored the RNA expression levels of IKZF family genes in the transcriptional atlas of 49 tumorous MF skin lesions from a previously published cohort of our group ( 19 ). This cohort comprised 49 patients with tumour stage MF, of whom 27 patients were diagnosed with MF with large cell transformation (LCT).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the expression pattern of the IKZF family in CTCL, this study explored the RNA expression levels of IKZF family genes in the transcriptional atlas of 49 tumorous MF skin lesions from a previously published cohort of our group ( 19 ). This cohort comprised 49 patients with tumour stage MF, of whom 27 patients were diagnosed with MF with large cell transformation (LCT).…”
Section: Resultsmentioning
confidence: 99%
“…When α-synuclein interacted with microglia and migrated to the lysosome, α-synuclein alone did not activate microglia or elicit an in ammatory response, and CD4+ T cells had to be added to α-synuclein-treated microglia to elicit a strong immune response, suggesting that α-synuclein triggers the immune response The involvement of CD4+ T cells is crucial in the process of the α-synuclein-triggered immune response [2]. In our results, has-miR-3180-3p-regulated CBX8 is involved in cellular communication and immune response regulation and affects CD4+ T cell depletion [7]; has-miR-3180-3p-regulated GPSM1, which encodes the activator of Gprotein signalling 3 (AGS3), regulates G-protein signalling in the immune system and thus regulates the activation process of T cells[8]; has-miR-20a-3p-regulated aberrant expression of PEG10 increased T cell size and promoted T cell proliferation and in ltration [9]; has-miR-20a-3p-regulated TPM2 was signi cantly and negatively correlated with the degree of CD8+ T cell in ltration [10]; the mutation of PGM3 which regulated by hsa-miR-20a-3p have recently been shown to lead to disorders of glycosylation, lymphopenia and impairment in T cell proliferation [11]; has-miR-1281-regulated NCKAP1 is signi cantly associated with the level of T cell in ltration [12]. The above mRNAs are involved in T-cell activation and in ltration, and changes in the expression of these mRNAs produced under miRNA regulation may lead to impaired T-cell activation and reduced in ltration, which may eventually lead to an immune response by T cells absent of α-synuclein-activated microglia, and the inability of microglia to clear α-synucleinexpressing neurons in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic treatments can be combined with skin directed treatments to provide maximum cumulative efficacy without cumulative toxicity ( 40 ). Recent studies have revealed that ectopic expression of paternally expressed gene 10 (PEG10) in large cell transformation (LCT) malignant T cells and suggested that PEG10 inhibition may serve as a promising therapeutic approach for patients with advanced CTCL ( 41 ). Nowadays, for patients with CTCL, allogeneic hematopoietic stem cell transplantation has been the only curative treatment ( 42 ).…”
Section: Discussionmentioning
confidence: 99%